Optimization of the pore structure of biomass-based carbons in relation to their use for CO2 capture at low and high pressure regimes - Sevilla, Marta; Al-Jumialy, Abdul Salam M.; Fuertes, Antonio B.; Mokaya, Robert (American Chemical Society, 2018)
A versatile chemical activation approach for the fabrication of sustainable porous carbons with a pore network tunable from micro- to hierarchical micro-/mesoporous is hereby presented. It is based on the use of a less corrosive and less toxic chemical, i.e. potassium oxalate, than the widely used KOH. The fabrication procedure is exemplified for glucose as precursor, although it can be extended to other biomass derivatives (saccharides) with similar results. When potassium oxalate alone is used as activating agent, highly microporous carbons are obtained (SBET ~ 1300 - 1700 m2 g-1). When a melaminemediated activation process is used, hierarchical micro-/mesoporous carbons with surface areas as large as 3500 m2 g-1 are obtained. The microporous carbons are excellent adsorbents for CO2 capture at low pressure and room temperature, being able to adsorb 4.2 - 4.5 mmol CO2 g-1 at 1 bar and 1.1 - 1.4 mmol CO2 g-1 at 0.15 bar. On the other hand, the micro-/mesoporous carbons provide record-high room temperature CO2 uptakes at 30 bar of 32 - 33 mmol g-1 CO2 and 44 - 49 mmol g-1 CO2 at 50 bar. The findings demonstrate the key relevance of pore size in CO2 capture, with narrow micropores having the leading role at pressures < 1 bar and supermicropores/small mesopores at high pressures. In this regard, the fabrication strategy presented here allows fine-tuning of the pore network to maximize both the overall CO2 uptake and the working capacity at any target pressure.